Osnutek bipolarnega mikroprocesorja - Breznik, G. (Informatica (Ljubljana), 1980)
The article describes a 16-bit bipolar microprocessor with 2900 family elements. The processor has a parallel 2 x 8-bit construction and is thus universal for all standard-format data coded in the two's complement. The system has a horizontal microinstruction. By development and testing procedures an host-computer was used. Developed were microprogrammes for basic mathematical functions with fixed- and floating-point using a symbol record. The example shows multiplication of two 16-bit numbers.
Keywords: bipolarni mikroprocesorji; programiranje